Complications of interventional cardiovascular procedures : a case-based atlas - Bailey, Steve R.; Colombo, Antonio , 1950-; Moussa, Issam D. (Demos Medical, 2012)
An atlas that covers the potential complications for the range of interventional cardiovascular procedures. It presents each complication with a case example: case description; how it was dealt with; why it happened; and, a discussion of whether and how it could have been avoided in this case.